Assessment of Distribution and Threats to Two Threatened Pheasants in the Brein Nishat Conservation Reserve, Kashmir, India - Shansaz, Umer Hameed; F. Fazili, Mustahson; Bhat, Bilal A. (New Visions in Biological Science Vol. 5, 2021)
Two pheasant species; Himalayan monal (Lophophorus impejanus) and koklass (Pucrasia macrolopha) were observed during extensive surveys in Brein Nishat Conservation Reserve (BNCR) with an average altitude of 2300-3400m (7545-11155ft). The dawn call count approach was used to observe koklass, whereas the transect walk method was used to observe Himalayan monal. The majority of sightings occurred in densely forested areas with coniferous vegetation and grassy litter less in mixed vegetation. Locality wise abundance was obtained and ER was found to be high in areas of dense vegetation and far from human sight. The threat to pheasants was associated with anthropogenic pressure around the BNCR's periphery, followed by predator threat.